2008
DOI: 10.1345/aph.1k522
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir Hypersensitivity Reaction: an Update

Abstract: Serious adverse events associated with the use of abacavir can be avoided by appropriate recognition and management of the HSR. Screening patients for HLA-B(*)5701 prior to initiation of abacavir represents a tool to further decrease the risk of HSRs as well as unnecessary discontinuation of this drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…Recently, candidate gene studies and genomewide analyses have identified several genetic markers associated with increased hepatotoxicity risk. Thus, flucoxacillin-induced hepatotoxicity is closely linked to HLAB5701 (15), the same allele responsible for susceptibility reactions to abacavir, which is present in at least 4% of Caucasian Europeans (16). Estrogen-induced cholestasis is associated with mutations in gene ABC B11, which codes for the bile salt export pump (17), and valproate-related liver toxicity is linked to mutations in the gene encoding mitochondrial DNA polymerase gamma, POL G1 (18).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recently, candidate gene studies and genomewide analyses have identified several genetic markers associated with increased hepatotoxicity risk. Thus, flucoxacillin-induced hepatotoxicity is closely linked to HLAB5701 (15), the same allele responsible for susceptibility reactions to abacavir, which is present in at least 4% of Caucasian Europeans (16). Estrogen-induced cholestasis is associated with mutations in gene ABC B11, which codes for the bile salt export pump (17), and valproate-related liver toxicity is linked to mutations in the gene encoding mitochondrial DNA polymerase gamma, POL G1 (18).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Abacavir hypersensitivity syndrome is characterized by gastrointestinal symptoms including nausea, vomiting, abdominal cramping, respiratory symptoms including coughing and shortness of breath and constitutional symptoms including fever, body rash and weight loss 3 . Some studies have also linked abacavir to an increased risk of myocardial infarction 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Abacavir is a nucleoside reverse transcriptase inhibitor that has been prescribed to almost 1 million HIV patients during the past decade and which is used in combination with other medications to treat HIV infection (37). In white populations, hypersensitivity reaction (HSR) occurs within the first 6 weeks of therapy in 5%-8% of patients receiving this drug.…”
Section: Hypersensitivity Reactions and Variations Of Major Histocompmentioning
confidence: 99%